2007
DOI: 10.1530/eje-06-0662
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction is related to insulin resistance and inflammatory biomarker levels in obese prepubertal children

Abstract: Background: The metabolic syndrome (MS) is associated with insulin resistance (IR), a systemic lowgrade inflammatory state and endothelial dysfunction. These disorders may arise at a very early age in obese children. This study aimed to investigate the relationship between endothelial dysfunction and both IR and inflammation in prepubertal obese children. Methods and results: Von Willebrand factor (vWF) and soluble intercellular adhesion molecule-1 (sICAM-1) levels were measured in 46 obese prepubertal childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…The presence of low-grade inflammation in obese childrenthat appeared in this studywas evaluated by measuring serumconcentrationsof CRP and IL6,as both showed a highly significant difference compared to the non-obese children and a very strong positive correlation with each other and with HOMA-IR and BMI.In agreement with thisJiménez et al [31],Sonya et al [32],Olzaet al [33], andValle et al [34]; all affirmed that the levels of these inflammatory markers are elevated in prepubertal obese children and that are associated with insulin resistance with the subsequent possibility of development of diabetes and cardiovascular disease. Additionally, Oliveira et al [35] agreed this finding and added that CRP is strongly related with metabolic syndrome and its components including insulin resistance in obese youth.Semiz et al also approved this finding and stated that CRP correlated with BMI and BP which are risk factors for coronary heart disease, supporting the relationship between obesity, inflammation and atherosclerosis [36].IL-6 is an inflammatory cytokine that stimulates the hepatic productionof CRPthis can explain the state ofinflammationassociated with obesity, and could mediate, at least partially,obesity-related insulin resistance [37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The presence of low-grade inflammation in obese childrenthat appeared in this studywas evaluated by measuring serumconcentrationsof CRP and IL6,as both showed a highly significant difference compared to the non-obese children and a very strong positive correlation with each other and with HOMA-IR and BMI.In agreement with thisJiménez et al [31],Sonya et al [32],Olzaet al [33], andValle et al [34]; all affirmed that the levels of these inflammatory markers are elevated in prepubertal obese children and that are associated with insulin resistance with the subsequent possibility of development of diabetes and cardiovascular disease. Additionally, Oliveira et al [35] agreed this finding and added that CRP is strongly related with metabolic syndrome and its components including insulin resistance in obese youth.Semiz et al also approved this finding and stated that CRP correlated with BMI and BP which are risk factors for coronary heart disease, supporting the relationship between obesity, inflammation and atherosclerosis [36].IL-6 is an inflammatory cytokine that stimulates the hepatic productionof CRPthis can explain the state ofinflammationassociated with obesity, and could mediate, at least partially,obesity-related insulin resistance [37].…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, Desideri et al [42] reported an association between the two variables in obese children older than those studied here. Moreover, Jiménez et al suggested that CRP, IL-6 and ICAM-1 are molecular markers associated with atherosclerosis and its progression [31].…”
Section: Discussionmentioning
confidence: 99%
“…While the relation between obesity and both raised C-reactive protein (CRP) [4,5] and decreased adiponectin (including high-molecular-weight adiponectin) levels [6,7,8,9,10] in children is well documented, studies examining IL-6 levels in overweight children show conflicting findings [8,11,12,13]. Obese prepubertal Turkish children have significantly elevated IL-6 levels compared to lean controls [11], and Herder et al [12] showed a significant association between IL-6 levels and BMI (adjusted for age, sex and lipids) in a large cohort of German adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…But HOMA-IR levels and incidence of hyperinsulinsm were significantly higher in obese children. CO and IR are also characterized by impaired immunity and a low-grade inflammation status depending on the multicellular release of cytokines, adipokines, and reactive oxygen species [1,[6][7][8][15][16][17]. We thought that dry eye may be correlated with obesity in these children based on the role of this inflammation leading to overweight and obesity.…”
Section: Methodsmentioning
confidence: 99%
“…IR is more frequent in children with very high BMI [5]. IR is considered to be a chronic low-grade inflammation [6,7]. We hypothesized that dry eye, as an inflammatory disease, may be correlated with obesity in these children based on the role of this inflammation leading to overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%